Quality in Molecular Biology Testing for Inherited Thrombophilia Disorders - Cooper, Peter C.; Goodeve, Anne C.; Beauchamp, Nicholas J. (Seminars in Thrombosis and Hemostasis, 2012)
As the understanding of the genetic basis of the inherited thrombophilias has increased over recent years, their routine diagnostic genetic analysis has also matured. This review considers methods used to test for the factor V (F5) Leiden mutation and prothrombin 20210A (F2 c.*97G>A) allele, and analysis of the SERPINC1, PROC, and PROS1 genes in cases of antithrombin, protein C (PC), and protein S (PS) deficiency, respectively. Issues relating to quality are explored, highlighting where analytical and sample handling errors may occur. Detection of the factor V Leiden mutation and the prothrombin c.*97G>A allele are best performed using real-time polymerase chain reaction analysis as this relatively simple technique allows their discrimination from rare variants of neighboring nucleotides; not possible using the more time-consuming restriction digestion assays. With the advent of low-cost and high-throughput sequence analysis, direct sequencing has become the first-line method to provide a definitive diagnosis of inherited, rather than acquired, deficiencies. Large cohort studies have shown that antithrombin and PC mutations are identified in between 61 and 87% of patients, whereas the detection rate in PS deficiency is substantially lower in around 40% of patients. Large gene deletions make up between 7 and 10% of PS and antithrombin mutations and only 1% of PC mutations, but it is suggested that dosage analysis techniques such as multiplex ligation-dependent probe amplification should be used for all three genes as part of routine analysis to ensure mutations are not missed. Best practice guidelines are available from EuroGentest covering a wide variety of the issues raised in this review and all laboratories should participate in appropriate external quality assurance schemes to ensure they continue to offer high quality service.
Keywords: mutation; polymorphism; genetic analysis; external quality assessment; quality control